An Effect of temperature on the spread of Covid-19 in Qatar, Kuwait and other Gulf countries - Abujazar, Maha; Al-Awadhi, Shafiqah; Rachdi, Mustapha; Bensmail, Halima (Kuwait Journal of Science, 2022)
Background: COVID-19 has emerged as a serious pandemic that emerged during since the end of 2019. The dissemination and survival of coronaviruses have been demonstrated to be affected by ambient temperature in epidemiological and laboratory research. The goal of this investigation was to see if temperature plays a role in the infection produced by this novel coronavirus. Methods: Between March 29, 2020, and September 29, 2020, daily confirmed cases and meteoro-logical parameters in many Gulf countries were collected. Using a generalized additive model, we investigated the nonlinear relationship between mean temperature and COVID-19 confirmed cases.. To further investigate the association, we employed a piecewise linear regression. Results: According to the exposure-response curves, the association between mean temperature and COVID-19 cases was nearly linear in the window of 21 − 30◦C while it is almost flat beyond that window. When the number was below 21◦C (lag 0-14), each 1◦C increase was associated with a 4.861 percent (95 percent CI: 3.209 − 6.513) increase in mean temperature (lag 0-14). Our sensitiv-ity analysis confirmed these conclusions. Conclusions: Our findings show a positive linear association between mean temperature and the number of COVID-19 cases with a threshold of 21◦C. There is little evidence that COVID-19 case numbers would rise as the weather becomes colder, which has important consequences for making health strategy and decision.